Gambaran Hasil Pemeriksaan HCG Metode Imunokromatografi dan Aglutinasi Lateks pada Sampel Urin Pagi pada Ibu Hamil Trimester Pertama - Yonahara Farahita; Tantri Ramadan; Yoen Ubay Maulidias Sudarjo; Nafi Izza Putri; Arimbi Eka Saputri; Ica Fikri Musyarofah; Zalfa Aliyah Salsabilah; Fu'ad Minan Zuhri (Jurnal Analis Kesehatan Kendari, 2026)
Pregnancy is a physiological process characterized by an increase in Human Chorionic Gonadotropin (HCG) hormone concentrations in blood and urine, making HCG examination essential for early pregnancy detection. This study aimed to describe the results of HCG examination using immunochromatography and latex agglutination methods on morning urine samples from first-trimester women in pregnancy. This research used a cross-sectional, descriptive observational design carried out at Banyumas Regency’s Medical Laboratory Technology Laboratory. The study population consisted of first-trimester pregnant women, with a total sample of 24 respondents selected using purposive sampling. Morning urine samples were examined using immunochromatography and latex agglutination methods according to standard operating procedures, and the results were provided as frequency and percentage distributions after a descriptive analysis. The results showed that all samples tested positive using the immunochromatography method, indicating the presence of HCG in all respondents. The latex agglutination method demonstrated varying HCG titers, with the highest frequency observed at a dilution of 1:32, reflecting differences in HCG concentration among samples. These variations were influenced by gestational age and increasing hormone levels during the first trimester. It can be concluded that both immunochromatography and latex agglutination methods are effective in detecting HCG in morning urine samples of first-trimester pregnant women. It is recommended to use morning urine and appropriate testing methods to obtain optimal early pregnancy detection results.